Exploring Nagusamegusa (1418): The semiotics of encounter and exchange for a poet-traveller in Muromachi Japan - Shino PA (International Academic Forum)
The paper applies the conference theme of 'exchanges and encounters' to a 15th century Japanese travelogue, Nagusamegusa (‘Grasses of Consolation', 1418), by the influential poet and Zen priest Shōtetsu (1381-1459). There is a great richness and diversity of exchanges and encounters on many different levels to be found in the work; on the present occasion the paper examines two types of such encounters for their encoded significance in historical, social and cultural terms. Firstly, on the most concrete level, Shotetsu's travel from Kyoto to sojourn in the provinces brings him into contact with a surprisingly colourful cast of characters representing many different strands of Muromachi society. In particular he is lionised by a local feudal magnate for his literary pedigree. The paper interprets this experience in terms of the highly transitional, symbiotic and socially mobile characteristics of Muromachi society, and the penetration of the culture of the capital into the provinces, and warrior uptake of aristocratic tradition. However, on the level of spiritual and artistic exchange, the journey is also one where, in addition to the physical and topographical, Shotetsu encounters and responds to the cultural landscape of the literary past: in this journey the stages of his travel are marked by tributes to utamakura, or places famed in poetry; his need to compose poetry at such richly literary sites show his culturally-determined drive to construct a ‘proper' identity for himself as a poet in the classical mode through interaction with the canonised voices of the past. Thus the paper uses the content of a historical and literary document, Nagusamegusa, as a vehicle to demonstrate the semiotics of encounter and exchange.